Antibiotic Adsorption by Metal-Organic Framework (UiO-66): A Comprehensive Kinetic, Thermodynamic, and Mechanistic Study - Mossab K. Alsaedi; Ghada K. Alothman; Mohammed N. Alnajrani; Omar A. Alsager; Sultan A. Alshmimri; Majed A. Alharbi; Majed O. Alawad; Shahad Alhadlaq; Seetah Alharbi (MDPI AG, 2020)
Bacterial antibiotic resistance has been deemed one of the largest modern threats to human health. One of the root causes of antibiotic resistance is the inability of traditional wastewater management techniques, such as filtration and disinfection, to completely eliminate residual antibiotics from domestic and industrial effluents. In this study, we examine the ability of UiO-66; a metal-organic framework (MOF); in removing the antibiotic Doxycycline from aqueous environments. This study's findings suggest that UiO-66 was able to remove nearly 90% of the initial Doxycycline concentration. To correlate the isothermal data, Langmuir and Freundlich models were used. It was determined that the Langmuir model was best suited. Pseudo-first and -second order models were examined for kinetic data, where the pseudo-second order model was best suited-consistent with the maximum theoretical adsorption capacity found by the Langumir model. Thermodynamic analysis was also examined by studying UiO-66 adsorption under different temperatures. Mechanisms of adsorption were also analyzed through measuring adsorption at varying pH levels, thermogravimetric analysis (TGA), Infrared spectroscopy (IR) and Brunauer-Emmet-Teller (BET). This study also explores the possibility of recycling MOFs through exposure to gamma radiation, heat, and heating under low pressure, in order for UiO-66 to be used in multiple, consecutive cycles of Doxycycline removal.